Assessment of the Remaining Carbon Budget: A Comparison of a Simple Response Model and the MAGICC Model. - Martinsen, Andreas Rostrup (UiT The Arctic University of Norway, 2020)
We are changing the global climate by altering the Earths energy balance through the emission of greenhouse gasses. The international community aims to prevent dangerous warming with mitigative efforts. A remaining carbon budget (RCB) can roughly quantify an allowable amount of emissions for keeping the temperature below a set target. We have built a simple climate model using impulse response functions and parameterizations of the forcing of atmospheric radiatively active agents. The Simple Response Model (SRM) emulates CMIP5 ensemble models over several SSP emission scenarios. We deliver compelling visualization of the risk of warming associated with carbon budgets using probability density functions around TCREs. The risk of warming and uncertainty in the carbon budget increase with less ambitious targets. By comparing the SRM with the Model for the Assessment of Greenhouse Gas Induced Climate Change (MAGICC) model, we verify the SRMs results. Results from incorporating regional Arctic amplification show more substantial uncertainties and more damaging temperature responses. We added possible nonlinear effects into the model framework, proving it possible under reasonable levels of additional forcing. The linearity of the TCRE falls apart for strongly nonlinear Earth system feedbacks.